2017
DOI: 10.1037/per0000156
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory examination of emotion regulation skill strengthening in borderline personality disorder.

Abstract: This study examined whether individuals with borderline personality disorder (BPD; N = 25) exhibit deficits in their ability to strengthen their emotion regulation skills over time compared with healthy controls (HCs; N = 30). Participants were instructed to implement 1 of 2 different emotion regulation strategies (i.e., distraction and mindful awareness of the emotion) or to either react naturally (i.e., nonregulation condition) in response to BPD-relevant stimuli across multiple trials. Self-reported negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…No significant decrease in HF-HRV during the EWMT as compared to resting-state was found, which resembles earlier findings of studies using emotion regulation tasks (Dixon-Gordon et al, 2011 ; Fitzpatrick & Kuo, 2016 ; Krause-Utz, Walther, et al, 2019 ; Kuo et al, 2016 ; Metcalfe et al, 2017 ; Svaldi et al, 2012 ). At the same time, we observed significant group differences in HF-HRV.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…No significant decrease in HF-HRV during the EWMT as compared to resting-state was found, which resembles earlier findings of studies using emotion regulation tasks (Dixon-Gordon et al, 2011 ; Fitzpatrick & Kuo, 2016 ; Krause-Utz, Walther, et al, 2019 ; Kuo et al, 2016 ; Metcalfe et al, 2017 ; Svaldi et al, 2012 ). At the same time, we observed significant group differences in HF-HRV.…”
Section: Discussionsupporting
confidence: 87%
“…With regards to BPD, previous research on HF-HRV revealed inconsistencies, partly due to methodological differences in study design and sample characteristics. During rest, patients with BPD showed reduced HRV (Koenig et al, 2016 ), while changes during emotion regulation tasks have not consistently been found (Dixon-Gordon, Chapman, Lovasz, & Walters, 2011 ; Fitzpatrick & Kuo, 2016 ; Krause-Utz, Walther, Lis, Schmahl, & Bohus, 2019 ; Kuo, Fitzpatrick, Metcalfe, & McMain, 2016 ; Metcalfe, Fitzpatrick, & Kuo, 2017 ; Svaldi, Dorn, Matthies, & Philipsen, 2012 ). Not all studies in BPD controlled for childhood trauma, comorbid PTSD and medication, which may all influence HF-HRV (Krause-Utz, Walther, et al, 2019 ; Meyer et al, 2016 ; O’Regan, Kenny, Cronin, Finucane, & Kearney, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…HF-HRV differences dependent on the ER instruction, in BPD. Likewise, patients with BPD previously showed no differences in HRV when implementing and strengthening ER skills (Svaldi et al ., 2012; Metcalfe et al ., 2015; Fitzpatrick and Kuo, 2016; Kuo et al ., 2016; Dixon-Gordon et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with BPD showed reduced baseline RSA but did not differ from HC during the ER task, indicating a similar adaptation to distressing conditions. Similarly, other data suggest that individuals with BPD do not significantly differ in implementing ER skills (Metcalfe et al ., 2015; Fitzpatrick and Kuo, 2016). Moreover, and unlike HC, they showed increased HRV when instructed to accept ( v. suppress) emotional experiences during social rejection (Dixon-Gordon et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas HCs reported greater positive affect during distraction than mindfulness, the BPD group showed no difference in positive affect between the two strategies (Kuo et al, 2016). Furthermore, both groups experienced increased effectiveness of distraction, but not mindfulness, in reducing negative affect over time (Metcalfe et al, 2017). Overall, the effectiveness of the ER strategies reduced as participants encountered increasingly arousing stimuli, though this relationship was stronger for HCs during mindfulness than for participants with BPD during either strategy .…”
Section: Distraction and Mindfulnessmentioning
confidence: 86%